Biologics and immunomodulators for treating Crohn's disease developing after surgery for an initial diagnosis of ulcerative colitis: a review of current literature. (3rd July 2018) - Yadav, Abhijeet; Foromera, Joshua; Falchuk, Kenneth R.; Feuerstein, Joseph D.
Abstract: Crohn's Disease (CD) or CD-like (CDL) conditions of the pouch are rare long-term inflammatory complications of patients who were initially diagnosed with ulcerative colitis (UC) who undergo total proctocolectomy with ileo-anal anastomosis (IPAA). There are no societal guidelines nor a consensus on their treatment, resulting in significant challenges for clinicians for their diagnosis and management. It is important to differentiate them from other more common pouch-related complications like pouchitis, cuffitis, irritable pouch syndrome, surgery associated stricture, and fistula. In this review, we focus on the less common presentation of CD and CDL conditions of the pouch and their treatment with the use of anti-TNF therapy with or without immunomodulator.